Investigation of the efficacy of mesenchymal stem cell-derived conditioned medium on wound healing through scratch test and teer analysis - AKSU, MEHMET BURAK (My University, 2023)
The aim is to investigate how Umbilical Cord-Derived Mesenchymal Stem Cells conditioned medium (UC-MSC-CM) can promote wound healing and epithelial barrier function. UC-MSCs were differentiated into osteocytes, adipocytes, and chondrocytes to determine their multipotency. Flow cytometric analyses confirmed positive surface markers (CD90, CD73, CD105) and the absence of negative markers (CD34, CD11b, CD19, HLA_DR). We prepared conditioned medium (CM) from these cells. UC-MSC CM was tested in in vitro wound healing experiments using scratch assays and transepithelial electrical resistance measurements at 6th, 12th, and 24th hours to assess its regenerative effects. UC-MSCs were found to be multipotent in the characterization and differentiation analysis, demonstrating their potential for use in regenerative medicine. In our wound model design, UC-MSC-CM significantly accelerated the healing process 75% and 92.7% at 12 and 24 hours respectively compared to the control group. According to TEER analyzes epithelial barrier resistance showed 200 Ω.cm2 with UC-MSC-CM healing process at the 12th and 24th hours while the control group showed 145 Ω.cm2 and 185 Ω.cm2 at the same time points, respectively. The study demonstrates the potential of UC-MSCs in repairing epithelial barriers and wound injuries. The UC-MSC-CM accelerates wound closure as the healing process advances and enhances barrier integrity and permeability. These findings highlight UC-MSC-CM as a cell-free therapy for regenerative medicine and wound healing. Further research should focus on understanding the underlying mechanisms and optimizing its therapeutic applications to revolutionize wound management and treatment.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); conditions medium; scratch assay; TEER analysis; Umbilical cord derived mesenchymal stem cell; wound healing